An innovative material based on natural rubber and leather tannery waste to be applied as antistatic flooring - Ruiz, Marcos R. [UNESP]; Budemberg, Eduardo R. [UNESP]; Cunha, Giovanni P. da; Bellucci, Felipe S. [UNESP]; Cunha, Helder N. da; Job, Aldo E. [UNESP] (Wiley-Blackwell, 2015)
In recent decades, the production chain of beef and bovine leather has grown significantly because of an increase in the world's population and improved access to consumption. However, the generation of waste derived from this sector has grown simultaneously, and consequently, improved ways of adding value, reusing, and disposing these waste materials are being sought. In this article, we present a new and innovative composite material based on vulcanized natural rubber (NR), carbon black (CB), and leather waste (NR/CB/leather). The NR/CB/leather composites were prepared by thermal compression with 60 phr of CB and 60 or 80 phr of leather waste. In accordance with Brazilian sanitary laws, we exposed these composites for 24 h to bleach (B) and a disinfectant with the aim of simulating a true everyday cleaning use. The deconvolution of the impedance semicircles was carried out, and two relaxation phenomena around linear relaxation frequencies of about 10(5) and 10(6) Hz were found and associated mainly with charge carriers from CB and leather waste. With the addition of leather, the electrical conductivity of the composites increased two orders of magnitude from 5.70 x 10(-6) for the NR/CB to 7.97 x 10(-4) S/cm for NR/CB/leather-60 phr B. These results point to the possibility of using these composites as an antistatic flooring once they exhibit acceptable values of electrical conductivity and once they withstand, from the structural, morphological, and electrical point of view, exposure to sanitizing agents. Furthermore, the production of these composites will add value to and enable an environmentally acceptable disposal of leather waste. (c) 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41297.
Keywords: applications; composites; elastomers; properties and characterization; rubber